LEXICAL VS CONCEPTUAL BLENDS: HOW TO RECONCILE THE TWO? - Mierzwińska-Hajnos, Agnieszka (Acta Neophilologica, 2017)
The objective of this paper is to apply a revised model of conceptual integration as proposed by Brandt and Brandt [Brandt and Brandt 2005, 3, 216-249; Brandt 2013] to the analysis of recently coined neologisms expressed in the form of lexical blends. Assuming that lexical blending is one of the most productive word-formation processes [Lehrer 2003, 15, 369-382; Lehrer 2007, 115-133; Gries 2004, 415-428], the question arises whether it should be considered solely for morphological analysis, or rather viewed as a cognitively entrenched phenomenon. The case of Polish Miserikordyna that is to be scrutinized within the course of the proposed analysis opts for the latter, thus giving conceptual blends priority over lexical blends. To prove this, the analysis of the proposed neologism will be carried out with the aid of a six-space model as delineated by Line Brandt and Per Aage Brandt. It is going to be proved that lexical blends involve more than a morphological operation since the process of their creation starts at the conceptual level and is inextricably bound with on-line processing and on-line decoding. Therefore, the Brandt and Brandt model seems an appropriate framework as it may contribute to a more thorough interpretation and ultimate understanding of various instances of such lexical blends.